In Silico Analysis of Candidate Genes Involved in Lignin Biosynthesis from Woody Species and Phylogenetic Relationship - Wong, Lai Kuan (Universiti Malaysia Sarawak, UNIMAS, 2010)
The lignin biosynthesis genes are highly conserved throughout vascular plants and thus it can provide useful information to better understand the evolution of land plants. Three Angiosperm trees namely Arabidopsis thaliana, Populus trichocarpa, Eucalyptus globulus, and a gymnosperm tree, Pinus taeda were selected in this study. Motif and domain for each gene were identified by scanning it with PROSITE and Pfam databases. In this study, only six of the genes: 4CL, CAD, PAL, C3H, C4H and F5H have motif identified and represented in regular expression. The motif in regular expression can be used to estimate the protein function. Domain analysis showed that two lignin proteins; COMT, CAD are multidomains proteins while C3H, C4H and F5H shared the same domain, p450 which involve in oxidative metabolism of natural compounds. The phylogenetic analyses were carried out using two different approaches implemented in MEGA software: distance based (NJ) and character based (MP). The phylogenetic analysis of lignin genes showed the divergence between angiosperm and gymnosperm species.